Persistent cognitive and affective alterations at late withdrawal stages after long-term intermittent exposure to tobacco smoke or electronic cigarette vapour: Behavioural changes and their neurochemical correlates. (August 2020) - Ponzoni, Luisa; Braida, Daniela; Carboni, Lucia; Moretti, Milena; Viani, Paola; Clementi, Francesco; Zoli, Michele; Gotti, Cecilia; Sala, Mariaelvina
Graphical abstract: Highlights: Balb/c mice exposed to e-CIG or CIG show marked long-term deficits in cognitive and affective-like behaviour at late withdrawal times. In late withdrawal, hippocampal levels of AMPA subunits and scaffold protein PSD 95 are decreased. Crf/CrfR1 levels in the hippocampi of e-CIG or CIG mice are increased after exposure and greatly decreased after 60 days of withdrawal. Both e-CIG and CIG induce similar behavioural and neurochemical alterations during both dependence and withdrawal phases. Abstract: Smoking cessation induces a withdrawal syndrome associated with anxiety, depression, and impaired neurocognitive functions, but much less is known about the withdrawal of e-cigarettes (e-CIG). We investigated in Balb/c mice the behavioural and neurochemical effects of withdrawal for up to 90 days after seven weeks' intermittent exposure to e-CIG vapour or cigarette smoke (CIG). The withdrawal of e-CIG and CIG induced early behavioural alterations such as spatial memory deficits (spatial object recognition task), increased anxiety (elevated plus maze test) and compulsive-like behaviour (marble burying test) that persisted for 60–90 days. Notably, attention-related (virtual object recognition task) and depression-like behaviours (tail suspension and sucrose preference tests) appeared only 15–30 days after withdrawal and persisted for as long as up to 90 days. At hippocampal level, the withdrawal-induced changes in the levels of AMPA receptor GluA1 and GluA2/3 subunits, PSD 95 protein, corticotropin-releasing factor (Crf) and Crf receptor 1 (CrfR1) mRNA were biphasic: AMPA receptor subunit and PSD95 protein levels initially remained unchanged and decreased after 60–90 days, whereas Crf/CrfR1 mRNA levels initially increased and then markedly decreased after 60 days. These late reductions correlated with the behavioural impairments, particularly the appearance of depression-like behaviours. Our findings show that major behavioural and neurochemical alterations persist or even first appear late after the withdrawal of chronic CIG smoke or e-CIG vapour exposure, and underline importance of conducting similar studies of humans, including e-CIG vapers.